In vitro and in vivo evaluation of chitosan-alginate/gentamicin wound dressing nanofibrous with high antibacterial performance. (February 2020) - Bakhsheshi-Rad, H.R.; Hadisi, Z.; Ismail, A.F.; Aziz, M.; Akbari, M.; Berto, F.; Chen, X.B.
Abstract: Wound dressings based on nanofiber polymer scaffolds with good antimicrobial performance and skin reconstruction ability are promising options to thwart wound infection and accelerate wound healing. This paper reports on the synthesis via electrospinning of chitosan-alginate (CS-Alg) nanofiber dressings with various amounts of gentamicin (Gn; 0–10 wt%) as a drug delivery system. Smooth and continuous nanofibers with no obvious beads were created, with increases in the amount of Gn resulting in reduced fiber diameter. Antimicrobial tests showed the Gn-loaded nanofibers had good antibacterial performance as indicated by the inhibition of bacterial growth. CS-Alg nanofibers loaded with higher Gn concentrations exhibited greater antibacterial performance than those with lower Gn concentrations. In vitro cell culture studies demonstrated that CS-Alg wound dressings with 1–3% Gn improved L929 cell attachment and proliferation more than wound dressings with higher Gn concentrations. In vivo experiments revealed that Cs-Alg nanofibers loaded with 3% Gn significantly enhanced skin regeneration in a Balb/C mice model by stimulating the formation of a thicker dermis, increasing collagen deposition, and increasing the formation of new blood vessels and hair follicles. Collectively, Gn-loaded CS-Alg wound dressings can be considered a good candidate for drug delivery systems and skin regeneration applications. Graphical abstract: Image 1 Highlights: Chitosan-alginate/gentamicin wound dressing nanofibrous is fabricated via the electrospinning method. CS-Alg/Gn fibrous exhibited greater antibacterial performance than those with lower Gn. CS-Alg-(1–3)Gn mats showed higher cell attachment and proliferation than mats with higher Gn. CS-Alg-3Gn wound dressing enhanced skin regeneration in a Balb/C mice model. Antibacterial mechanism of the CS-Alg-Gn wound dressing nanofibrous is proposed.